BS O07 Secondary Hyperparathyroidism Before and After Bariatric Surgery: a Prospective Study with 2-Year Follow-Up. (7th December 2022) - Salman, Mohamed; Tourkey, Mohamed; Noureldin, Khaled; Khalid, Sadaf; Issa, Mohamed; Elewa, Ahmed; Shaaban, Hossam; Salman, Ahmed; Elsherbiney, Mohammed; Elhaj, Mujahid; lee, Shiela; Gebril, Mahmoud
Abstract: Background: Secondary hyperparathyroidism (SHPT) is linked to obesity. Bariatric surgery may be associated with calcium and vitamin D deficiencies leading to SHPT. This study aimed to detect the prevalence of SHPT before and after bariatric surgery Methods: This prospective study assessed the prevalence of SHPT after sleeve gastrectomy (SG, n = 38) compared to one anastomosis gastric bypass (OAGB, n = 86). All patients were followed up for two years. Bone mineral density (BMD) was assessed using dual-energy X-ray absorptiometry. Results: Of the 124 patients, 71 (57.3%) were females, and 53 (42.7%) were males, with a mean age of 37.5 ± 8.8 years. Before surgery, 23 patients (18.5%) suffered from SHPT, and 40 (32.3%) had vitamin D deficiency. The prevalence of SHPT increased to 29.8% after 1 year and 36.3% after 2 years. SHPT was associated with lower levels of vitamin D and calcium and higher reduction of BMD in the hip but not in the spine. After 2 years, SHPT was associated with a significantly lower T-score in the hip. SHPT and vitamin D deficiency were significantly more common in patients subjected to OAGB compared to SG (p = 0.003 and p < 0.001, respectively). There is a strong negative correlation between vitamin D levels and parathormone levels before and after surgery. Conclusions: The prevalence of SHPT is high in obese patients seeking bariatric surgery, especially with lower vitamin D levels. Bariatric surgery increases the prevalence of SHPT up to 2 years. Gastric bypass is associated with a higher risk of developing SHPT compared to SG.